2018
DOI: 10.1002/osp4.169
|View full text |Cite
|
Sign up to set email alerts
|

Obesity, underweight and BMI distribution characteristics of children by gross national income and income inequality: results from an international survey

Abstract: SummaryBACKGROUNDEconomic wealth and income inequality may impact on childhood BMI distribution by affecting overconsumption of food and sedentary forms of transportation and entertainment across the whole or some of the population.OBJECTIVESTo determine whether BMI distribution of children differs by gross national income (GNI) per capita and Gini index derived from World Bank data.METHODSSecondary analysis of largely self‐reported height and weight data from a multi‐country, cross‐sectional study (ISAAC), of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 26 publications
1
7
1
Order By: Relevance
“…Factors such as overconsumption of food among children in higher socioeconomic families in developing countries leads to the risk of excessive weight gain [36]. Economic wealth and income inequalities also impact childhood development as they usually use private transportation rather than walking and engage in sedentary entertainment such as video games, which influence their energy balance [39].…”
Section: Discussionmentioning
confidence: 99%
“…Factors such as overconsumption of food among children in higher socioeconomic families in developing countries leads to the risk of excessive weight gain [36]. Economic wealth and income inequalities also impact childhood development as they usually use private transportation rather than walking and engage in sedentary entertainment such as video games, which influence their energy balance [39].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Beal et al [20] have recently found that higher per capita income was linked to a greater prevalence of childhood excess weight in Vietnam. Thus, income inequality could affect childhood obesity, through an increase in excessive food intake, as well as in a more sedentary lifestyle which could favour the development of overweight/obesity [1,53,54]. However, caution is needed when interpreting the results because of certain aspects.…”
Section: Discussionmentioning
confidence: 99%
“…Second, these authors used different criteria to determine per capita income, as well as different cut-off points. Third, the per capita income indicator may vary depending on the analysed country and presents certain limitations to describe wealth inequalities (e.g., gross national income or Gini index) [53].…”
Section: Discussionmentioning
confidence: 99%
“…Data from the Chinese Health and Nutrition Survey (CHNS) in the period 1989 to 2011 showed that an increased Gini index was associated with higher risks of having abnormal obesity [30]. Among 205,388 girls aged 13–14 years from 36 countries, those from higher income inequality countries had a greater median BMI [31]. BMI was closely correlated to CRF among children and adolescents.…”
Section: Discussionmentioning
confidence: 99%